Urban integration of aeroelastic belt for low-energy wind harvesting - Aquino, Angelo I.; Calautit, John Kaiser; Hughes, Ben Richard (Elsevier, 2017)
In this modern age low-energy devices are pervasive especially when considering their applications in the built-environment. The multitude of low-energy applications extend from wireless sensors, radio-frequency transceivers, charging devices, cameras and other small-scale electronic devices. The energy consumptions of these devices range in the milliwatt and microwatt scale which is a result of continuous development of these technologies. Thus, renewable wind energy harnessed from the aeroelastic effect can play a pivotal role in providing sufficient power for extended operation with little or no battery replacement. An aeroelastic belt is a simple device composed of a tensioned membrane coupled to electromagnetic coils and power conditioning components. This simplicity of the aeroelastic belt translates to its low cost and overall modularity. The aim of this study is to investigate the potential of integrating the aeroelastic belt into the built environment using Computational Fluid Dynamics (CFD) simulations. The work will investigate the effect of various external conditions (wind speed, wind direction and physical parameters, positioning and sizing) on the performance of the aeroelastic belt. The results from this study can be used for the design and integration of low-energy wind generation technologies into buildings.